Development and Validation of the Spectrophotometric Method for the Quantitative Determination of Azlocillin in Pure Substance and Medical Preparation (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The kinetic of conjugated reactions of S-oxidation and perhydrolysis of Azlocillin (Azl) withpotassium caroate in alkaline medium is studied by the increase of forming product light absorbance at 275 nm.Materials and Methods: SecuropenÂ® - powder Azl sodium in flacons for the preparation of solution for injections(Azl 1.0 g and 5.0 g) was used for analysis. Peroxymonosulfate acid as triple potassium salt 2ÐšÐSO5âˆ™ÐšÐSO4âˆ™K2SO4(OxoneÂ®) of â€œextra pureâ€ qualification was used as oxidant. A scheme of peroxyacid oxidation and perhydrolysisconjugated reactions of Azl by means of potassium caroate is proposed. A new spectrophotometric method forthe quantitative determination of sodium Azl in SecuropenÂ® preparation using potassium caroate (KHSO5) as ananalytical reagent was proposed. Results: At pH 2â€“3 for 1 mole of penicillin, 1 mole of KHSO5 is consumed,and the quantitative interaction is achieved within a time of more than 1 min (observation time). The results wereobtained by the recommended procedure for seven replicate titrations of mixtures containing the three speciesat various concentrations. Relative standard deviation (RSD) = (0.96â€“2.02) %, Î´ = (+0.49 â€¦ â€“ 0.33)%. It canbe seen that Azl can be determined successively with good accuracy and reproducibility. Conclusions: The newprocedure was developed and the ability of quantitative determination of penicillin in pharmaceutical preparationSecuropenÂ® by spectrophotometric method using potassium caroate (KHSO5) as analytical reagent was shown.